What Drives Local Food Prices? : Evidence from the Tanzanian Maize Market - Baffes, John (World Bank, Washington, DC, 2015)
This study quantifies the relationship between Tanzanian and external maize markets while also accounting for domestic influences. It concludes that external influences on domestic prices originate from regional, rather than global, markets. It also shows that, compared to external factors, domestic factors exert a greater influence on Tanzanian maize markets. Further, the mechanisms through which trade policies influence maize markets involve interactions with both external market shocks and domestic weather shocks. Overall, it provides evidence that the intermittent imposition of export bans in Tanzania has had adverse impacts on its maize markets, and consequently, on the development of its agrarian economy.